The Effect of Corneal Irregularity on Astigmatism Measurement by Automated versus Ray Tracing Keratometry. Issue 13 (April 2015) - Roh, Hyun Cheol; Chuck, Roy S.; Lee, Jimmy K.; Park, Choul Yong; Jhanji., Vishal
<x xml:space="preserve">Abstract</x> Abstract The aim of this study was to compare the effect of corneal irregularity on astigmatism assessment using automated keratometry (AK) (IOLMaster) versus ray tracing keratometry (Pentacam). This is an observational case series approved by the institutional review board of Dongguk University Hospital, Goyang, South Korea. A total of 207 eyes of 207 cataract patients were included. Preoperative corneal astigmatism was measured by both IOLMaster and Pentacam. Corneal irregularity index (IR) was calculated in Fourier analysis map of Pentacam. AK by IOLMaster and total corneal refractive power (TCRP, 3 mm and 4 mm zone analysis with pupil centered) by Pentacam were selected and the difference between the 2 measurements (delta Δ) was calculated using vector analysis. Ocular residual astigmatism (ORA) after cataract surgery was calculated by subtracting 6-month postoperative refractive astigmatism (RA) measurements from corresponding preoperative values (AK, TCRP3, and TCRP4). The mean irregularity index measured was 0.042 ± 0.019 mm (mean ± standard deviation) and was positively correlated with age and magnitude of corneal astigmatism (P < 0.001 and P < 0.05). The difference (Δ) between TCRPs and AK (ΔTCRPs-AK) was 0.43 ± 0.37 (TCRP3) and 0.39 ± 0.35 (TCRP4) diopters. Linear regression analysis revealed that age (P < 0.001), IR (P < 0.001), and AK (P < 0.001) were positively correlated with ΔTCRPs-AK. In highly irregular corneas (IR over 0.77 diopters: mean + 2 standard deviation), postoperative ORAs calculated using TCRPs were significantly lower than ORAs calculated using AK. Corneal irregularities significantly impact astigmatism assessment by IOLMaster (AK) and Pentacam (TCRPs). Compared with AK, TCRPs were more accurate in predicting postoperative residual astigmatism in highly irregular corneas.